A comprehensive guide to loop-mediated isothermal amplification, an emerging diagnostic tool for plant pathogenic fungi - Németh, Márk Z.; Kovács, Gábor M. (Frontiers in Plant Science, 2025)
The detection and identification of plant pathogenic fungi are crucial for effective plant protection measures. In the past two decades, loop-mediated isothermal amplification (LAMP) has emerged as a simple and cost-efficient tool for plant disease diagnosis, overcoming many drawbacks of traditional and PCR-based methods. LAMP relies on efficient DNA synthesis at a constant temperature, eliminating the need for thermocycling equipment. It is typically more robust, specific, and sensitive than PCR. This literature review summarizes LAMP primer design, reaction protocol development, sensitivity and specificity testing, and result detection methods. We provide examples of how LAMP’s advantages are exploited in disease diagnosis and survey its diverse applications in plant pathogenic fungi research. These applications include the detection, identification, and monitoring of plant pathogenic fungi; the replacement of culture-based methods; the detection of genetic regions associated with functional changes; and the detection of single nucleotide polymorphisms. A comprehensive list of available assays is also provided. Despite its shortcomings—including difficulties with primer design, risks of cross-contamination, and the potential for false positives—LAMP holds significant potential to gain widespread recognition and popularity in the study of plant pathogenic fungi.